PENGEMBANGAN PENUNTUN PRAKTIKUM FISIOLOGI TUMBUHAN MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS MUSLIM MAROS - Wiwin Pramita Arif; Sri Maya (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
The aim of this study is to develop a valid, practical, and effective practicum guide of Plant Physiology for students of Biology Education Department at Universitas Muslim Maros. This is a research and development (R&D) with Plomp development model. The research has 5 stages, namely: (1) the initial investigation phase; (2) design phase; (3) realization / construction phase; (4) test, evaluation and revision phases; (5) and implementation phase. The results show a valid, practical, and effective criteria of the product for students in practicum use. Based on the results, this product can be carried out in practicum activities as it can improve student skills. The product was tested on Biology Education students at the Muslim University of Maros of Academic Year of 2018/2019. The results indicate that the practicum guides fulfilled the valid criteria with an average content validity of 0,93, with the implementation category of 3 which was mostly implemented, and effective with 80.95% where the students learning achievements above 70.